The solubility of helium in lead–lithium eutectic alloy. (June 2022) - Sedano, L.; Esteban, G.A.; Cavaro, M.; Iraola, E.; Abdulrahman, A.; Batet, L.; Guasch, M.
Highlights: The He solubility value needed to evaluate helium saturation conditions and bubble nucleation in nuclear fusion liquid metal blankets. He solubility values in lead and lead–lithium eutectic proposed by using semi-empiric correlations sustained on cohesion models and historic data for Li, Na, K and Hg. Satisfactory soundness of semi-empirical correlation based on Kumaŕs cohesion model to approach available historic measurements. New experimental approaches needed to confirm the low values obtained. Abstract: The helium production rates in liquid metals (Pb-Li eutectic alloy, LLE and others) Blanket Breeders (BB) are nearly mol-to-mol linked to tritium and intimately associated with the compulsory requirement of high tritium self-sufficiency of next fusion reactors. When LLE is oversaturated and the helium solubility limit is exceeded, helium atoms can nucleate in the form of bubbles. The presence of helium bubbles within LLE channels could have severe impact on the diverse BB designs, in particular on tritium transport permeation and its recovery. Even though He is an inert gas assumed to be insoluble, the helium Henry's constant ( KH ) in a liquid metal is not zero. The very low KH and difficulties to measure it has historically driven to the absence of basic data. A semi-empirical correlation is proposed providing the helium solubility (i.e.: the helium Henry's constant) based on Kumar's cohesion model using the available thermo-physical experimental solubility data for lithium, sodium, potassium, mercury. The proposed expression for eutectic lead–lithium is: K H at . fr . Pa - 1 = 5.99 · 10 - 4 exp ( - 1.16 · δ k ) exp - 54.23 / RT, being KH the Henry's constant; T [K], R [8.314 10 -3 kJ mol −1 K −1 ] and δk the Kumar's cohesive parameter. From a δk justified value of 18.2 MPa 1/2 in LLE the values for KH range from 1.14·10 -17 to 1.35·10 -15 at.fr.Pa −1 for temperatures between 350 and 870C. The helium solubility should integrate the lead–lithium eutectic nuclear material database for fusion systems design.